Sendai framework for disaster risk reduction: Success or warning sign for Paris? - Jaroslav Mysiak; Swenja Surminski; Annegret Thieken; Reinhard Mechler; Jeroen Aerts (Fondazione Eni Enrico Mattei (FEEM), 2015)
In March 2015, a new international blueprint for disaster risk reduction (DRR) has been adopted in Sendai, Japan, at the end of the Third UN World Conference on Disaster Risk Reduction (WCDRR, March 14 - 18, 2015). We review and discuss the agreed commitments and targets, as well as the negotiation leading the Sendai Framework for DRR (SFDRR) and discuss briefly its implication for the later UN-led negotiations on sustainable development goals and climate change.
Keywords: Q5; Q54; 330; Disaster Risk; World Conference on Disaster Risk Reduction; Sendai Framework for Disaster Risk Reduction